Internet of Things Performance using Raspberry Pi for Body Temperature and ECG with GPS - Shaban, Fahad Ahmed; Ahmed, Marwa Riyadh (Journal of Information Systems Research and Practice, 2024)
This paper aims to discuss how the research produced unique results that are comparable to the results of traditional devices for ECG and blood temperature, as well as the patient’s location. It does this by examining previous studies, the study’s criteria, and the proposed results. The majority of earlier research findings made it impossible to quickly and effectively compare patient data. Since all sensors must be used to show general results, the majority of earlier studies were unable to display results when only one sensor was used. The results of this study show that the most expensive traditional devices can be replaced with sensors and technologies that connect to the Internet of Things and Raspberry Pi to accomplish similar tasks with more flexibility when handling patient data. Aside from financial savings, integrating multiple sensors into a single device is a unique and innovative process that saves a much of time and effort. When handling his medical cases, the doctor can have more privacy thanks to the desktop system’s data security, which also keeps unwanted parties from accessing patient information.